1997
DOI: 10.1073/pnas.94.25.13493
|View full text |Cite
|
Sign up to set email alerts
|

Computer-based analysis of the binding steps in protein complex formation

Abstract: Computer models were used to examine whether and under what conditions the multimeric protein complex is inhibited by high concentrations of one of its components-an effect analogous to the prozone phenomenon in precipitin tests. A series of idealized simple ''ball-and-stick'' structures representing small oligomeric complexes of protein molecules formed by reversible binding reactions were analyzed to determine the binding steps leading to each structure. The equilibrium state of each system was then determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
2
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(120 citation statements)
references
References 21 publications
(21 reference statements)
6
111
2
1
Order By: Relevance
“…The problem of incomplete structures has been argued to be central to both DNA brick assembly 9,34-36 and protein complexes 27,37 . Indeed, before the experiments of ref.…”
Section: Resultsmentioning
confidence: 99%
“…The problem of incomplete structures has been argued to be central to both DNA brick assembly 9,34-36 and protein complexes 27,37 . Indeed, before the experiments of ref.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen bonding can be considered as a special case of dipole-dipole interaction that is usually stronger due to the relatively short distance ranges (2.5 to 3.5 Å) and angle constraints brought about as a result of the directional nature of nonbonding (lone pair) electron orbitals. The energy range for dipole-dipole interactions is about -3 to -5 kJ.mol -1 or between -0.7 and -1.2 kcal.mol -1 , whereas hydrogen bonding energies lie between -8 and -32 kJ.mol -1 , corresponding to between -2 and -8 kcal.mol -1 , although lower values have been reported in some cases [25]. As a particular example, the dipolar energy between tyrosine and camphor at an orientation found in the active site of cytochrome P450 cam (the enzyme which specifically mediates camphor 5-hydroxylation) can be calculated to be between -3.5 and -4.6 kcal.mol -1 depending on whether the experimental or calculated dipole moments are employed.…”
Section: Dipole-dipolementioning
confidence: 95%
“…Because of the pro-zone (combinatorial inhibition) effect, the concentration of functional complexes before signaling can be shown to have a maximum (28). However, the existence of a maximum for MAPK activation and its position cannot be inferred directly from this effect, because phosphorylation reactions increase the number of possible complexes, and free rather than bound MAPK-PP represents the signaling output.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed study of this ''pro-zone'' effect has been reported recently (28). The pro-zone effect (''combinatorial inhibition'' can be proposed as a more descriptive term) in terms of the scaffold-mediated MAPK activation means that at low scaffold concentration, when both kinases are in excess, formation of a functional complex containing both kinases is likely, whereas in excess of the scaffold, nonfunctional complexes containing none or only one of the kinases become relatively more abundant.…”
Section: Existence Of a Scaffold Concentration Optimal For Signalingmentioning
confidence: 99%